V-046 LAPAROSCOPIC SURGICAL MANAGEMENT OF AN HUGE DIAPHRAGMATIC HERNIA. (13th October 2022) - Costa, J; Monti, E; Latham, L; Marzorati, A; Odeh, M; Colombo, E M; Ballabio, A; Zanchetta, M; Inversini, D; Ietto, G; Carcano, G
Abstract: Introduction: Diaphragmatic hernias (DH) in most cases are the consequence of a diaphragmatic trauma causing a missed injury. Less frequently, DHs are congenital. Case Presentation: A 52 years old patient came to our attention due to a worsening severe dyspnea. A chest CT scan were performed, showing an extensive left-side DH. We present the video of the surgical procedure. The patient mentioned a severe left hemithorax trauma occurred almost twenty years before due to a motorbike accident. Possibly, a diaphragmatic injury was not diagnosed at the time. Subsequently, a Covid-19-related chronic cough resulting in a persistently increased intra abdominal pressure may have caused the herniation of abdominal viscera. The surgical procedure was laparoscopic. The whole greater omentum and most of the transverse colon were herniated and, after a thorough adhesiolysis between the herniated tissues and the left diaphragmatic crus, the DH was reduced. It was confirmed the presence of a 8 cm defect of the left hemidiaphragm, it was repaired with a absorbable continuous suture. A 08×10 cm Bio-A patch was positioned over. The herniated tissues were meticulously examined and showed no signs of damage. Conclusions: Diaphragm's injuries are unfortunately difficult to diagnose in an acute setting, thus remaining often unbeknownst to the surgeon. Some patients never develop any symptoms because of such missed diaphragmatic injuries. Some others instead, due to an increase in the intra abdominal pressure, may develop symptomatic DHs. In the latter case, surgical management becomes mandatory.